APLIKASI METODE BIDIMENSIONAL EMPERICAL MODE DECOMPOSITION (BEMD) UNTUK DATA GAYABERAT GUNUNG UNGARAN, INDONESIA - Fuad Tarmidzi; Agus Setyawan (Youngster Physics Journal, 2013)
Gravity method processing will obtained gravity anomaly which is combination between regional and local gravity anomalies that need to separate it for interpretation. Upward continuation method commonly used to separates regional and local gravity anomalies. Recently, the separation of these anomalies can be done with Bidimensional Empirical Mode Decomposition (BEMD) method which its calculation based on gravity anomaly profile. BEMD will separates gravity anomali profile based on its frequency that some sub-sinyal will obtained from it. On this research, BEMD method has been used to separate gravity anomaly of Ungaran Mountain dan the result of it compared with the result from Upward Continuation method. 5 Intrinsic Mode Function (IMF) and 1 residual were obtained from BEMD method, wherein IMF3 showed pattern of regional gravity anomali and IMF1 showed pattern of local gravity anomaly. With using these methods, obtained patterns were similar. Keywords: BEMD, Gravity anomalies, Ungaran, IMF